Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Strategi Pembelajaran Inkuiri di Sekolah Dasar - Isabella, Sonia; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The aims of the research is describe the improvement of integrated thematic learning process using inquiry learning strategies in elementary school. This classroom action research using quantitative and qualitative approaches. The subject of the research consist of teacher and 32 students that is use 2 cycle. Cycle I is use twice meeting and cycle II is use onetime meeting the cycle is use four stages that is plant, implementation, observation, and reflection. The result of planning observation in cycle I  is 79,16% (B) and it increase to be 94,44% (A)  in cycle II. The result of teacher aspect observation in cycle I is 79,68% (B)  and it increase to be 93,75% (A) in cycle II. The result of student aspect observation in cycle I is 76,56% (B)  and it increase to be 93,75% (SB) in cycle II. The learning outcomes in cycle I is 75,07(C) and it increase to be 88,15 (A) in cycle II. The research showed the Inquiry Learning Strategies can improve the integrated thematic learnig outcomes in Elementary School Keywords: Learning Outcomes,  Inquiry Learning Strategies